2015
DOI: 10.1080/11035897.2015.1055298
|View full text |Cite
|
Sign up to set email alerts
|

Root zone of a continental rift: the Neoproterozoic Kebnekaise Intrusive Complex, northern Swedish Caledonides

Abstract: Mafic magmatic rocks formed between ca. 615 and 560 Ma along the Neoproterozoic margins of Baltica and Laurentia are classically attributed to continental rifting heralding the opening of the Iapetus Ocean. We report new data for the Kebnekaise Intrusive Complex (KIC) exposed in the Seve Nappes in northern Sweden. The KIC consists of sheeted dolerite dykes and gabbroic bodies with mutually intrusive relations. Major and trace element data exhibit a transitional-to normal-mid-ocean-ridge basalt-type geochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 149 publications
(189 reference statements)
1
24
0
Order By: Relevance
“…Ages of mafic magmatism obtained by CA‐ID‐TIMS generally fall within the time interval 608 to 596 Ma (Figure ; Svenningsen, ; Baird et al, ; Kumpulainen et al, ), suggesting that most of the SDC was emplaced during a short time period similar to the duration of the breakup of the NALIP. A younger SIMS age of 578 Ma has, however, also been found at Kebnekaise (Kirsch & Svenningsen, ).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Ages of mafic magmatism obtained by CA‐ID‐TIMS generally fall within the time interval 608 to 596 Ma (Figure ; Svenningsen, ; Baird et al, ; Kumpulainen et al, ), suggesting that most of the SDC was emplaced during a short time period similar to the duration of the breakup of the NALIP. A younger SIMS age of 578 Ma has, however, also been found at Kebnekaise (Kirsch & Svenningsen, ).…”
Section: Discussionsupporting
confidence: 74%
“…Opening of the Iapetus Ocean occurred in stages between about 620 and 550 Ma, beginning with rifting of rocks now found mainly in Caledonian nappes on Baltica and ending with breakup of southern Iapetus between Laurentia and Gondwana (Cawood et al, ). Rifting and opening of the portions of the Iapetus between Laurentia and Baltica is constrained by dating of mafic as well as felsic rift‐related magmatic rocks in sedimentary basins and basement from both the Laurentian side (e.g., Dempster et al, ; Halliday et al, ; Kamo et al, ) and the Baltican side (Baird et al, ; Bingen et al, ; Kirsch & Svenningsen, ; Kumpulainen et al, ; Root & Corfu, ; Svenningsen, ; this study; Figure a). The oldest rift‐related age on the Baltican side is that of the Egersund dikes, 616 ± 3 Ma (Bingen et al, ), whereas the youngest dikes at around 578 ± 9 Ma has been found in the Kebnekaise area (Kirsch & Svenningsen, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…570 Ma; Shumlyanskyy et al, ), and several carbonatite and kimberlite complexes (590–520 Ma; Ernst & Bell, , Torsvik et al, ). The parental magmas to the Seiland Igneous Province include picrites similar to OIB and are often explained as deep, hot mantle plume melts (e.g., Larsen et al, ), whereas the origin of the dominantly tholeiitic basalts of the dyke complexes is debated (Andréasson et al, ; Baird et al, ; Hollocher et al, ; Kirsch & Svenningsen, ).…”
Section: The Cimp: Chronology and Backgroundmentioning
confidence: 99%